The Impact Of Application Of Human Resources Accounting In Reducing Costs And Reducing The Phenomenon Of Career Slack: An Applied Study In Industrial Companies - Ibrahim Al-Ezzi, Ammar Ghazi; Ibrahim Khalf, Amina; Hadi Utaiwi, Khawla (Opción, 2019)
Sagging employment (disguised unemployment) is the presence of inflation in the number of employees or employees in government institutions and depart- ments, whether they are industrial or service institutions to perform a specific job, and therefore, if this excess number is dispensed, there is no impact on that work neither in terms of quantity nor how this phenomenon has great risks to the progress and development of the institution, department, or em- ployer in which they work, because any development or progress in it depends on creativity at work and not inactivity and sitting only waiting for the salary to be received. Here comes the role of human resources accounting and its role in reducing production costs through the distribution of workers and employees in the need of these institutions for their specialties and expertise and the distribu- tion of surplus of them in other institutions that need their services and exper- tise and thus will in turn reduce production costs and achieve the goal of these institutions. The study reached several conclusions, one of the most important of that was through the study, which shows that there is persuasive unemploy- ment (job slack) by having some employees and workers receive their salaries and bonuses annually against a very weak production level and even if there is production in some factories, it does not cover the cost of their salaries and their wages. The most important recommendations were investing human resources that enhances the value of the company and its financial position as it leads to an increase in the company’s capital by investing their experiences in developing production or investing them in other companies that need their services to eliminate job slack (disguised unemployment).